Teaching Proficiency Through Reading and Storytelling - Navarro-García, Esther (My University, 2023)
The objective of this work is to design an English didactic unit for Primary Education scholars who study English as foreign language in Spain. This didactic unit will apply Teaching Proficiency through Reading and Storytelling (TPRS) methodology. This approach to second language (L2) teaching was developed by a North American teacher, Ray Blaine, it is strongly founded on Stephen Krashen L2 acquisition theories, and it disassociates itself from the traditional concepts of L2 teaching methods. The purpose of the didactic unit is to engage students in the cooperative design of a narrative guided throughout Teaching Proficiency through Reading and Storytelling. This creative process is used as a tool to improve the acquisition of the L2, especially the students’ oral skills. An analysis of the mentioned methodology was performed in order to comprehend this approach, its implications and the way in which it could be taken from theory to practice, creating a didactic unit for sixth graders. The author reached a well-founded conclusion regarding this method and deems it as a remarkable and resourceful way to improve the students’ L2 proficiency and firmly believes it can be successfully applied in accordance with the Spanish Primary Education curriculum.
Keywords: TPRS; comprehensible input; storytelling; teaching english; second language acquisition; Grado en Maestro en Educación Primaria